Frontiers in Ophthalmology and Ocular Imaging - Ziaei, Alireza (IntechOpen, 2019)
Imagination is the key to any discovery, and its presence in the science to improve vision is no exception. Vision science is racing forward, spurred on by a host of exciting novel research discoveries and the efforts of scientists. This book, a collection of reviewed and relevant research chapters, intends to provide readers with a comprehensive overview of the latest and most advanced findings in several aspects of ophthalmology, ophthalmic pathology, ocular imaging, and certain treatments and surgical strategies. It is an excellent, well-integrated review of treatment options in eye disease that aims to provide a thorough overview of the recent developments written by international authors. "Frontiers in Ophthalmology and Ocular Imaging" can be used as an important reference for clinically oriented ophthalmologists and scientists.